A Comparison between Drilling and Standard Penetration Test (SPT) Data to the Electrical Resistivity Sounding with Schlumberger Configuration in UNS Area - Sinta Nur Rizqi Listanti; Darsono Darsono; Yusep Muslih Purwana (Department of Physics, Sebelas Maret University, 2018)
The geophysics test using electrical resistivity method has been conducted in the area of UNS Campus to indicate the lithological of subsurface. This method is categorized as a Non-Destructive Test (NDT) due to the data acquisition is done at the ground level and no destruction during the test, which is more advantageous than destructive method such as drilling and SPT test. This study was performed with Schlumberger configuration in three location by electrical resistivity sounding. The acquisition data uses Resistivity meter OYO 2119 McOHM-EL with the track length is 100 m, while the data processing use IPI2Win to get a logarithmic graph between distance and resistivity and Origin to obtain graphic of resistivity and SPT. The result of this study indicates that electrical resistivity has a good correlation with SPT data. The electrical resistivity graph shows a linear increase along with increment of the depth, which is similar to the SPT graph. The slope difference at the first location is 2.44±1,197, the second location is 2.028±0.822, and the third location is 0.622±0.735.